Comparing Antioxidant Activity of Extracts and Gel Preparations Combination of Buas-buas Leaves (Premna serratifolia l.) and Secang Wood (Caesalpinia sappan) - Tarung, Albianus Febri; Cristin, Bella; Maulidia, Yuninta; Kamil, Insan; Syalsabila, Regitha Rianda; Isnindar, Isnindar (Majalah Obat Tradisional, 2023)
Indonesia is a tropical country that has exposure to ultraviolet rays from the sun throughout the year. This causes susceptibility to skin problems for the Indonesian population, including the vulnerability to aging of the skin due to exposure to ultraviolet rays for a long time. In the prevention of degenerative diseases and aging, antioxidants play an important role. Buas-buas and secang, which are plants from the West Kalimantan region, have very high antioxidant activity. Gel preparations are typically formulated as moisturizers with the aim of increasing water content in the stratum corneum, thus hydrating and maintaining skin pH. Hence, this study aimed to create a gel preparation combining buas-buas leaf extract and secang, effective as a moisturizing and anti-aging gel. The results of measuring the antioxidant activity of the combination of crude ethanol extracts of buas-buas leaves and secang wood with the results of the three formulas have very strong antioxidant activity, namely F1 at 0.0329 mg/ml, F2 at 0.0246 mg/ml, and F2 at 0.0246 mg/ml. F3 of 0.2282 mg/ml, and IC50 results for gel preparations for F1 3,8677 mg/ml, F2 4,3953 mg/ml, F3 4,396 mg/ml. The gel preparations produced in this study have the appearance and fulfill the evaluation requirements, except for the evaluation of spreadability.